Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Stuck on a homework question with mathematical induction, I just need some help factoring and am getting stuck.

$\displaystyle \sum_{1 \le j \le n} j^3 = \left[\frac{k(k+1)}{2}\right]^2$

The induction part is: $\displaystyle \left[\frac{k(k+1)}{2}\right]^2 +(k+1)^3$ is where I am having a problem.

If you could give me some hints as to where to go since I keep getting stuck or writing the wrong equation.

I'll get to $\displaystyle \left[{k^2+2k\over2}\right]^2 + 2{(k+1)^3\over2}$

Any push in the right direction will be appreciated.

share|improve this question

4 Answers 4

up vote 4 down vote accepted





share|improve this answer

I assume you mean that you're trying to show that $$1^3+\dots+k^3=\left[\frac{k(k+1)}2\right]^2,\tag{1}$$ as otherwise, it makes no sense. For the induction step, you're supposing that $(1)$ holds for some $k$, and wish to show that $$1^3+\dots+k^3+(k+1)^3=\left[\frac{(k+1)(k+2)}2\right]^2.$$ By $(1)$, we need only show that $$\left[\frac{k(k+1)}2\right]^2+(k+1)^3=\left[\frac{(k+1)(k+2)}2\right]^2,$$ or equivalently, that $$(k+1)^3=\left[\frac{(k+1)(k+2)}2\right]^2-\left[\frac{k(k+1)}2\right]^2.\tag{2}$$

Hint: $a^2-b^2=(a+b)(a-b)$ will let you rewrite the right-hand side of $(2)$ in a nicer way, without having to go through nearly as much polynomial multiplication.

share|improve this answer

$$\begin{align} \left(\frac{k(k+1)}{2}\right)^2+(k+1)^3=\frac{k^2(k+1)^2+4(k+1)(k+1)^2}{4}\\ =\frac{(k+1)^2(k^2+4k+4)}{4}\\ =\frac{(k+1)^2(k+2)^2}{4}\\ =\left(\frac{(k+1)(k+2)}{2}\right)^2\\ \end{align}$$

share|improve this answer

You have: $$ \begin{align*} \left[ \frac{n (n + 1)}{2} \right]^2 + (n + 1)^3 &= \frac{n^2 (n + 1)^2 + 4 (n + 1)^2 (n + 1)}{4} \\ &= \frac{(n^2 + 4 (n + 1)) (n + 1)^2}{4} \\ &= \frac{(n^2 + 4 n + 4) (n + 1)^2}{4} \\ &= \frac{(n + 2)^2 (n + 1)^2}{4} \\ &= \left[\frac{(n + 1) (n + 2)}{2} \right]^2 \end{align*} $$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.